Seismic Analysis of Minimum Separation Distance for Low-Rise Buildings in Padang City to Prevent Structural Collisions - Pratama, Ardi; Masrilayanti, Masrilayanti; Kurniawan, Ruddy; Apdeni, Risma (Indonesian Mechanical Electrical and Industrial Research Society (IMEIRS), 2025)
This study examines the minimum effective separation distance between buildings necessary to avert structural damage from building pounding in Padang City, an area particularly vulnerable to seismic events. The study examines 45 structures throughout five districts, classified into three categories according to their height-to-width (H/L) ratio: (0.5–1.0), (1.1–1.5), and (1.51–2.0). Three pairs of ground acceleration records—Imperial Valley-06, Tokachi-Oki Aftershock, and Tokachi-Oki Mainshock—were selected and calibrated to align with the target response spectrum of Padang City using linear time-history analysis. The research assesses structural displacement capacity and drift ratio to ascertain the necessary minimum separation distances. The findings reveal that the minimum separation distance for Category A (H/L: 0.5–1.0), Category B (H/L: 1.1–1.5), and Category C (H/L: 1.51–2.0) spans from 40 cm to 48.4 cm, with a suggested practical separation of 50 cm per building. A separation distance of 1 meter is recommended to reduce the risk of structural collisions during earthquakes. These findings serve as a technical reference for urban planners, engineers, and legislators, facilitating safer building designs, enhanced seismic resilience, and diminished structural damage in earthquake-prone regions.